Decision-making process towards real estate agents, landlords, and expatriate tenants' criteria with perspective from principal-agent theory - Niti Rattanaprichavej (Cogent Business & Management, 2023)
This study aims to analyse the details of the stages in the decision-making process of real estate agents to reconcile the landlords and expatriate tenants' criteria and to explain these relationships with the principal-agent theory. Using a qualitative approach, the research engaged in semi-structured, in-depth interviews with 30 agents actively working in real estate agencies with foreign tenants as their target market. The findings of this research showed significant results about the unique reasons and criteria regarding the decision-making processes of each party. Additionally, it also highlighted the strategies used in addressing the various needs of these parties. These strategies included having a variety of property options available, skillfully using effective techniques such as matching, probing, and translating during communication, making trade-offs between factors, and employing effective negotiation methods. From a theoretical standpoint, the study discussed several significant aspects. These included examining power imbalances and negotiation dynamics, maximising the principal's interests, addressing situations where there are double principals involved, and considering contextual factors that sometimes contradict the assumptions of the principal-agent theory.
Keywords: 650; decision-making; landlords; principal-agent theory; real estate agent; tenants